awareness of others as a fundamental basis in education and society (Revista Electrónica REDINE, 2019)
The purpose of this essay is to explain and publicize the awareness of otherness and its implication within society intrinsically in an educational encounter, from the teacher's point of view, knowing that it is already recognized as a social entity, in order to understand that the other is an equal being within diversity, and that we for that other are also another starting from the premise that human beings are social beings, and education is the core of a society. Education is the ideal means for the state to reach its goal: justice. It depends on whether or not he achieves his ideal. For Aristotle (2002). Education was infinite, more specifically said: "education never ends, it is a process of improvement and therefore that process never ends. Education lasts as long as the person's life lasts. "